THE SPIRITUAL SIGNIFICANCE OF BARZAKH IN THE QUR'AN: AN ANALYSIS OF QURAISH SHIHAB'S THOUGHT - Warnisyah Harahap, Elly; Drajat, Amroeni; Anzaikhan, M. (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This study explores the concept of Barzakh in the Qur'an, focusing on Surah Al-Mu'minun verses 99-100 and 46. The research aims to understand the differences between the grave and Barzakh, whether humans sleep or are punished in barzakh, and the spiritual implications of these concepts. The novelty of this study lies in addressing the spiritual purpose of Barzakh as a 'checkpoint,' a topic not yet comprehensively examined in scholarly journals. Although Quraish Shihab has extensively discussed this in various YouTube content, it has not been systematically analyzed in academic literature. This study is a library research project employing a qualitative approach. The methodology involves descriptive analysis and content analysis of Quraish Shihab's interpretations, particularly his exegesis in Tafsir Al-Misbah. The findings conclude that Barzakh is a waiting realm (checkpoint) where rewards or sins from the world continue to affect the deceased. The spiritual significance of Barzakh underscores the importance of one's life record, encouraging the increase of good deeds and the avoidance of sinful deeds.